Building A Global Information Assurance Program - Curts, Raymond J (CRC Press, 2009)
Governments, their agencies, and businesses are perpetually battling to protect valuable, classified, proprietary, or sensitive information but often find that the restrictions imposed upon them by information security policies and procedures have significant, negative impacts on their ability to function. These government and business entities are beginning to realize the value of information assurance (IA) as a tool to ensure that the right information gets to the right people, at the right time, with a reasonable expectation that it is timely, accurate, authentic, and uncompromised.